2021
DOI: 10.1007/s40519-021-01329-8
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder and social anxiety symptoms in Iranian preadolescents: a network analysis

Abstract: Purpose Network studies of eating disorder (ED) symptoms have identified central and bridge symptoms in Western samples, yet few network models of ED symptoms have been tested in non-Western samples, especially among preadolescents. The current study tested a network model of ED symptoms in Iranian preadolescents (ages 9 to 13), as well as a model of co-occurring social anxiety disorder (SAD) and ED symptoms. Method Preadolescent boys (n = 405) and girls (n = 325) completed the Children Eating Attitudes Test-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 97 publications
(147 reference statements)
1
16
0
Order By: Relevance
“…assessment of psychiatric comorbidities such as depression and anxiety [ 33 , 44 , 53 , 56 , 75 , 79 ], posttraumatic stress disorder [ 60 , 82 ], social anxiety disorder [ 76 , 99 ], obsessive- compulsive disorder [ 49 , 55 , 63 , 83 ], trait anxiety disorder [ 48 ], autism spectrum disorder [ 54 ], borderline personality disorder [ 41 ], and alcohol misuse [ 40 ];…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…assessment of psychiatric comorbidities such as depression and anxiety [ 33 , 44 , 53 , 56 , 75 , 79 ], posttraumatic stress disorder [ 60 , 82 ], social anxiety disorder [ 76 , 99 ], obsessive- compulsive disorder [ 49 , 55 , 63 , 83 ], trait anxiety disorder [ 48 ], autism spectrum disorder [ 54 ], borderline personality disorder [ 41 ], and alcohol misuse [ 40 ];…”
Section: Resultsmentioning
confidence: 99%
“…After all, the fact that EDs are much more common in women than in men is broadly known and documented [ 102 ], with reasons usually attributed to social pressure [ 103 ], adolescent turbulence, poor body concept, and role confusion [ 104 ]. Just one study involved only male participants [ 47 ], while few other papers reported a more heterogeneous (mostly nonclinical) sample with male participants within the range of 40–60% [ 33 , 53 , 55 , 60 , 71 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, many studies reported no differences in network structure nor in global strength with regards to different ED diagnoses (de Vos et al, 2021;Goldschmidt et al, 2018;Mares et al, 2021), age (Brown et al, 2020;Calugi et al, 2020;Sahlan, Williams, et al, 2021), and sex (Sahlan, Keshishian, et al, 2021;Sahlan, Williams, et al, 2021).…”
Section: Metric Definition Interpretationmentioning
confidence: 98%
“…After all, the fact that EDs are much more common in women than in men is broadly known and documented (Striegel-Moore et al, 2009), with reasons usually attributed to social pressure (Whiteman, 2016), adolescent turbulence, poor body concept, and role confusion (Hsu, 1989). Just one study involved only male participants (Forrest, Perkins, et al, 2019), while few other papers reported a more heterogeneous (mostly nonclinical) sample with male participants within the range of 40-60% (Bronstein et al, 2022;Kenny et al, 2021;Kinkel-Ram et al, 2021;Liebman et al, 2021;Perko et al, 2019;Sahlan, Keshishian, et al, 2021;Sahlan, Williams, et al, 2021).…”
Section: Collection Of Psychometric Datamentioning
confidence: 99%